Kampanye Lingkungan Waste Management di SMAS Nasional Bandung dalam Mendukung Penguatan Poin SDGs Nomor 12 - Rizky Ilhami; Taqwaty Firdausijah; Puspita Bunga Wiraloka (Jurnal Nusantara Berbakti, 2024)
By having broad insight, students are able to understand the global context and the relationship between various disciplines. They can develop thinking skills, explore various perspectives, and broaden their views on various problems. Therefore, to improve the quality of competent students, it is necessary to broaden their horizons through the delivery of knowledge in new perspectives and scopes. The waste management campaign program at SMAS Nasional Bandung is an initiative to introduce and improve students' understanding of how threatening the climate crisis is that is still happening. Through various activities such as workshops, discussions, and practices. These activities aim to provide insight into environmental issues in achieving a holistic understanding of the importance of waste management. By involving students actively in the campaign, this program encourages a deeper understanding of the waste management process from personal to industrial waste, especially in the city of Bandung, as a step in implementing the Sustainable Development Goals (SDGs) point number 12. Responsible Consumption and Production